Analysis of the Role of Community Health Promotion in Overcoming Stunting in Central Maluku Regency, Maluku - Hasib (Magenta Journal De Healthymedi, 2024)
This examine investigates the function of network fitness advertising in addressing stunting occurrence amongst kids in Central Maluku Regency, Maluku. A pass-sectional design with multistage cluster sampling turned into employed to accumulate data on demographic traits, fitness promotion practices, and stunting costs. Descriptive statistics, paired-samples t-check, regression analyses, ANCOVA, and Pearson correlation analyses were performed to research the records. Results revealed a mild stunting incidence, varying stages of maternal training and family income, and a enormous lower in stunting rates submit-intervention. Maternal education, household earnings, and participation in health schooling applications emerged as massive predictors of stunting prevalence. Differences in stunting fees throughout maternal education ranges have been also located. Significant terrible correlations had been observed between stunting prevalence and maternal vitamins information, in addition to family earnings. The look at underscores the significance of community-pushed, holistic tactics integrating education, earnings assist, and fitness promotion to combat stunting efficiently.